Transformasi Supervisi Pendidikan dalam Menjembatani Spiritualitas dan Technopreneurship di Era Kecerdasan Buatan - Jakfar , Moh. Ferdiyanto Ali; Arraisah, Fulviana; Baidowi, Ach.; Wahid , Abdul; Wafi, Abdul; Nurhadi, Ali; Mubah , Hilmi Qosim (re-JIEM (Research Journal of Islamic Education Management), 2026)
The integration of Artificial Intelligence (AI) in education demands a transformation of supervisory functions that balances technological innovation with human values. This study aims to explore the conceptualization of educational supervision at the intersection of spirituality and technopreneurship within AI-integrated learning environments. The method employed was a qualitative Systematic Literature Review (SLR) following the PRISMA 2020 protocol. A systematic search was conducted on the Scopus database with strict inclusion criteria, yielding 12 final articles assessed for quality using the Mixed Methods Appraisal Tool (MMAT). Synthesis results indicate significant conceptual fragmentation where literature remains separated between AI-technology domains and spiritual-value domains, without holistic integration or explicit discussion regarding technopreneurship. No comprehensive model was found bridging spiritual values with AI-based technopreneurship practices, and implementation challenges were reported in a fragmented manner per domain. This research provides theoretical, methodological, and practical contributions for developing an integrative supervision framework. It is concluded that transforming educational supervision in the AI era requires integrating spiritual values and entrepreneurial insights to create a holistic and sustainable ecosystem.